Visualizing of the structure of subject trends in Persian articles published during 2008–2012 in information organization domain - Mousavizadeh, Maryam; Bagheri, Masume; Bagheri, Mansure; Karbala aghaie Kamran, Masume (The International information & library review, 2013)
This research investigates structure of the subject trends in the Persian articles published during the period of 2008–2012 about “information organization” in Iranian journals and creates a semantic map for this domain. This structure has been considered in two sections: First, the weight of each subject term used in articles was indicated, and then the relationships amounts of terms were measured. Content analysis and weighting were used in the first section. The Vector Space Model formula was used in order to weight terms. In the second section, Co-term analysis was used, that is, the number of co-occurrence of any two terms in the same article. Then the term/document occurrence matrix of these terms was created and at last the relations significant between terms were measured by Pearson Correlation Coefficient. To illustrate the structure of information organization domain, Ucinet software was used. Findings show that high-weight categories in Persian articles are: “cataloging”, “information retrieval”, “information systems” and “authority files”. Furthermore through weighting, determined that in trends rate aspect, the terms “ontologies”, “cataloging”, “evaluation”, “Dewey Decimal Classification”, “fields”, “libraries and information centers” and “descriptors”, “Functional Requirements for Bibliographic Records”, “metadata elements” and “National library and archives of I.R. of Iran” are 10 highest-weight terms. Research findings about the relationships of terms show attention to “cataloging” by “IFLA” and “National library and archives of Iran” and critical approach to this subject. Some other findings about this show: “indexing” are considered by cataloging and thesauri, “metadata” are considered in web-based and information retrieval points of view, “ontologies” term is considered in approach of basic concepts, tools and relevance, and attention to some organizations such as “IFLA” and “National library and archives organization of Iran” besides “users” and their information needs. In terms of weighting and relationships between the subject terms in Persian articles, “cataloging” is in the center of information organization domain. The semantic map of information organization in Persian articles illustrates three region of subject area including: 1. Cataloging, 2. Ontologies, thesauri and information retrieval, and 3. Metadata and information retrieval. •The high-weight terms in information organization in Persian articles are ontologies, cataloging, and evaluation.•High-weight categories in these articles are cataloging, information retrieval, information systems and authority files.•Findings about the relationships of terms show critical approach to cataloging.•In terms of weighting and relationships between the terms, cataloging is in the center of information organization domain.•The semantic map shows 3 regions: Cataloging-Ontologies, thesauri & information retrieval-Metadata & information retrieval.